1993
DOI: 10.1111/j.1365-2907.1993.tb00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of past persecution and habitat changes on the numbers of Badgers Meles meles in Britain

Abstract: Data from a Badger sett survey undertaken in the mid-1980s were used to calculate the effects of past persecution and land-use changes on Badger numbers. The current British Badger population was estimated to be 41,894 4404 social groups; if the effects of past persecution were eliminated, the population could be 43,437 f 4731 social groups, an increase of 3.7%. Most of this increase relates to persecution in Norfolk and Suffolk last century. In Britain the Badger population is largely confined to those areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…The relationship between habitat and density has also been observed in many other studies (e.g. Thornton 1988, Reason et al 1993, Seiler et al 1995, Macdonald et al 1996, Virgós & Casanovas 1999, Kowalczyk et al 2000, Virgos 2001. Furthermore, Kowalczyk et al (2003) found a correlation between habitat (oak-lime-hazel forest) and home-range size and between earthworm abundance and badger density across Europe.…”
Section: Habitat Home-range Size and Badger Densitymentioning
confidence: 55%
See 1 more Smart Citation
“…The relationship between habitat and density has also been observed in many other studies (e.g. Thornton 1988, Reason et al 1993, Seiler et al 1995, Macdonald et al 1996, Virgós & Casanovas 1999, Kowalczyk et al 2000, Virgos 2001. Furthermore, Kowalczyk et al (2003) found a correlation between habitat (oak-lime-hazel forest) and home-range size and between earthworm abundance and badger density across Europe.…”
Section: Habitat Home-range Size and Badger Densitymentioning
confidence: 55%
“…Boutin 1984, 1990, Hulbert et al 1996, Okarma et al 1998, Feore & Montgomery 1999, Kowalczyk et al 2003, Prange et al 2004, Palphramand et al 2007. Because habitat quality affects home-range size and home-range size and density tend to correlate, badger density is affected, at least partly, by habitat quality (Kruuk & Parish 1982, Thornton 1988, Reason et al 1993, Macdonald et al 1996, Virgós & Casanovas 1999, Virgos 2001, Jepsen et al 2005. By determining how habitat characteristics influence home-range size and how home-range size and density are connected we can estimate badger density on the basis of habitat characteristics in different landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human settlements were concentrated in the "a priori" optimal habitats for badgers (800-1200 m altitude). Conversely, game areas were avoided and it is possible that badgers were influenced by human persecution (see Cresswell et al 1989, Reason et al 1993, especially in low mountain areas. In summary, badger rarity in our study area appears to be attributed to the overall low quality of the environment (70 % of these mountains were xeric holm oak forests and associated shrub) and the increase of human settlements in the Sierra de Guadarrama will probably affect badger populations through habitar loss and direct persecution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well studied throughout Occidental Europe, especially in the United Kingdom and The Netherlands (Kruuk 1989). Information is available about its distribution and status (Wiertz and Vink 1986, Cresswell et al 1989, Griffiths and Thomas 1993, Reason et al 1993, Smal 1993; aspects related to behavioural plasticity in different environmental conditions (Kruuk 1989); diet (Kruuk 1989, Roper 1994; and sett distribution in relation to habitat characteristics (Zejda and Nesvadbova 1983, Thornton 1988, Skinner et al 1991a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation